Translokasi Hukum di Indonesia Koeksistensi Beberapa Sistem Hukum - Hari, Purwadi (Jurnal Hukum Progresif, 2005)
This study aims to explain translocation of laws that cause mixed legal system. Indonesian law is therefore an intriguing mixed legal system, blending civilian rules fashioned, in style, structure and content, with the common law, the law of islam and folk law. Both civil law and common law system, islamic legal system and folk law make valuable constributions to mixed legal system. The research was conducted by using comparative law method.